2017
DOI: 10.1021/acs.jnatprod.7b00704
|View full text |Cite
|
Sign up to set email alerts
|

Zampanolide Binding to Tubulin Indicates Cross-Talk of Taxane Site with Colchicine and Nucleotide Sites

Abstract: The marine natural product zampanolide and analogues thereof constitute a new chemotype of taxoid site microtubule-stabilizing agents with a covalent mechanism of action. Zampanolide-ligated tubulin has the switch-activation loop (M-loop) in the assembly prone form and, thus, represents an assembly activated state of the protein. In this study, we have characterized the biochemical properties of the covalently modified, activated tubulin dimer, and we have determined the effect of zampanolide on tubulin associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
(144 reference statements)
1
10
0
Order By: Relevance
“…Our high-resolution structure of cyclostreptin-bound tubulin together with new MS-HPLC experiments performed at a higher resolution challenge our previous hypothesis of cyclostreptin binding to βAsn228 and βThr220 [6] and instead demonstrates that cyclostreptin unequivocally interacts with βHis229, a residue which is known to be responsible for the lack of sensitivity of yeast tubulin to paclitaxel [30]. In fact, given the key role of βAsn228 in stabilizing the guanine nucleotide at the E-site with two hydrogen bonds, a cyclostreptin interaction with this residue would severely affect nucleotide binding, which is not the case [31]. There is also no evidence supporting the βThr220 adduct we observed previously [6].…”
Section: Discussionmentioning
confidence: 89%
“…Our high-resolution structure of cyclostreptin-bound tubulin together with new MS-HPLC experiments performed at a higher resolution challenge our previous hypothesis of cyclostreptin binding to βAsn228 and βThr220 [6] and instead demonstrates that cyclostreptin unequivocally interacts with βHis229, a residue which is known to be responsible for the lack of sensitivity of yeast tubulin to paclitaxel [30]. In fact, given the key role of βAsn228 in stabilizing the guanine nucleotide at the E-site with two hydrogen bonds, a cyclostreptin interaction with this residue would severely affect nucleotide binding, which is not the case [31]. There is also no evidence supporting the βThr220 adduct we observed previously [6].…”
Section: Discussionmentioning
confidence: 89%
“…Extensive studies showed that taccalanolides AF and AJ covalently bind to the taxane-site on β-tubulin [25,27]. Notably, to date, only three other microtubule stabilizing agents, zampanolide, dactylolide, and cyclostreptin, have been reported to react covalently with tubulin [28,29]. Taccalonolide AJ covalently interacted with tubulin in a similar manner to cyclostreptin [27].…”
Section: Tubulin Binding Sitesmentioning
confidence: 99%
“…Apart from the taxanes (paclitaxel, docetaxel, and cabazitaxel, and an albumin bound paclitaxel nano‐droplet formulation [Abraxane®]) only the aza‐epothilone B analog ixabepilone has been approved . Recently, drugs covalently binding to the taxoid site of tubulin (in particular to aminoacids H229β, N228β, and D226β lining one side of H7) such as zampanolide, dactylolide, and taccalonolide AJ have also appeared, but despite the potential benefits of a different mechanism of action, longer lifetimes, and less clearance, they have not yet reached the clinic.…”
Section: Tubulin As a Targetmentioning
confidence: 99%